Impact of Teachers' Pedagogical Content Knowledge on Learner Outcomes in Libode Sub-District, South Africa - Mjobo, Nobabalo Mandisa; Cishe, Elphina Nomabandla; Omojemite, Matthew Damilola (CV Sinergi Ilmu dan Publikasi, 2025)
The effectiveness of reading instruction in the Foundation Phase (FP) is critical for developing learners' reading abilities. Despite this, FP teachers often face challenges related to their pedagogical content knowledge (PCK), teaching methods, and lesson preparation. This study investigates the impact of teachers' pedagogical content knowledge on learner outcomes in Libode Sub-District. The study was quantitative research which involved the use of descriptive research design. The population of the study was 200 teachers. Systematic random sampling was used to select forty (40) Grade 3 teachers. Teachers from all participating schools were allocated numbers 1 - 200, which were put in a hat. The main question addressed by the study requires the understanding of the contribution of FP teachers’ lack of reading pedagogical content knowledge to Grade 3 learners’ inability to read EFAL texts. Data were evaluated using analytical and logical reasoning to examine each component of data provided. The study's findings reveal a significant challenge in stimulating reading both inside and outside the classroom. Teachers in this group encounter difficulties that may be due to factors such as limited resources, insufficient parental involvement, and inadequate professional development. It was recommended that schools increase the availability of diverse reading resources, enhance parental involvement, provide targeted professional development for teachers, and promote student-centered approaches to reading instruction.